Kinetic study of palm oil mill effluent (POME) treatment by activated sludge - Wun, Wee Long; Chua, Gek Kee; Chin, S. Y.; N., Zainol (Universiti Malaysia Pahang, 2019)
Kinetic parameter is a basis for design and optimization of activated sludge POME treatment. In fact, most of the kinetic parameter value used in design and optimization are default values taken from municipal wastewater. The kinetic parameters for POME treatment have not been thoroughly studied and most of the system is using the Activated Sludge Models (ASM), either in modeling or design. Thus, the kinetic study of POME treatment by activated sludge system were carried out to obtain the kinetic parameters for the POME treatment plant design calculation. In this study, POME treatment was carried out in batch studies into 14 L aeration tank with activated sludge for the biological oxidation process with optimum pH at 6.5 ± 0.1, MLVSS of 2000 ± 200 mg/L for HRT of 48 h and feeding with 650 ± 20 mg BOD3/L of anaerobic treated POME, while SRT was controlled at a range of 10 days to 20 days with interval of 2 days for the kinetic study experiment. From this kinetic study, the kinetic parameters for COD and BOD basis had been determined for maximum yields coefficient (Y), endogenous decay coefficient (kd), maximum specific substrate utilization rate (k) and half-velocity constant (Ks) at 0.2369 mg VSS/mg COD, 0.1060 day-1, 2.2717 day -1 and 758.7705 mg/L for COD basis whilst the kinetic parameters value for BOD basis were 0.6718 mg VSS/mg BOD3, 0.0658 day-1, 1.4136 day-1 and 556.1526 mg/L, respectively. Sicne the BOD is one of the discharge parameters in discharge regulatory, thus kinetic parameters for BOD basis will be used for the system design of POME treatment.